Morphological feature of Pelagia noctiluca (Forskål, 1775) (Cnidaria: Scyphozoa) in western Libyan coast, Tripoli - Abushaala, Najla; Elfituri, Abdulfattah; Ben Abdullah, Abdullah; Shtewi, Hanan (Journal of Pure & Applied Sciences, 2022)
The Jellyfish cnidarians are important consumers of zooplankton in the Mediterranean Sea previously known. The aim of this study is to classification this species of jellyfish and examination morphological structure. The samples were collected from the Tripoli coast of Libya in September 2018 by scoop net. The number of samples was 31 individuals, collected to study the morphological structure measurements and wet weight. The results of the morphological structure showed the diameter of medusa 2.3 - 13.4cm, while the total length was 4.5 - 17cm, and the length of four oral arms was 2.4 - 12.9cm, the length of eight tentacles was 1.8 - 15cm and wet weight was 2.0 -73g. Based on morphological features and classification, the species was identified as Pelagia noctiluca (Forskål, 1775), but the differences between individuals in medusa size and wet weight indicate refers to different ages. So, this species is considered the first appearance on the Libyan coast.